HR Analytics and Employee's Performance Management: An Assessment built on existing literature - Chaudhary, Brijendra; Srivastava, Shweta (Future Science / FSH-PH Publications, 2021)
This paper attempts to study how HR Analytics affects employee performance management based on existing research. The literature analysis has led to a clear understanding that many traditional HR functions are now transforming. However, the transition is slow and will take significant energy from HR and its management to keep the change momentum intact. This literature analysis has explored the increased use of HR Analytics in modern-day companies and analyses change speed.